Pengaruh Budaya Organisasi terhadap Kinerja Karyawan: Studi pada Perusahaan - Agus Wahyudi; Nurul Azizah; Nisa’ Shafira al Zahra; Nanin Erlina; Alberto Halomoan (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the impact of organizational culture on employee performance in various companies. Organizational culture, which includes values, procedures, and norms adopted by members of the organization, has a crucial role in achieving company goals. The methodology used is a quantitative approach with data collection through surveys distributed to employees. The results of the analysis show that organizational culture has a positive and significant effect on employee performance, with a calculated t value that is greater than the t table, indicating a strong correlation between the two variables. Characteristics of a good organizational culture, such as innovation, respect for individuals, and an orientation that will occur, have been shown to increase employee productivity and job satisfaction. This study concludes that companies need to develop and manage a positive organizational culture to improve employee performance holistically.